Non-invasive intracranial pressure assessment using shear-wave elastography in neuro-critical care patients. (May 2022) - Xu, Guohui; Wu, Xuehai; Yu, Jian; Ding, Hong; Ni, Zilong; Wang, Yong
Highlights: Young's modulus of the optic nerve was not correlated with sex, age or BMI. Young's modulus of the optic nerve was higher during Valsalva maneuver. Young's modulus of the optic nerve reflected changes in intracranial pressure. Abstract: Objective: To determine if Young's modulus of the optic nerve (ON) structure as measured by shear-wave elastography can suggest changes in intracranial pressure (ICP) in neuro-critical care patients. Materials and methods: Thirty-one healthy volunteers and twenty-two neuro-critical care patients were enrolled. ON sheath (ONS) diameter (ONSD) values and Young's modulus measurements of volunteers were collected in a calm state and during a Valsalva maneuver (VM). Ultrasound measurements and ICP values of patients were collected on operation day and at 24 and 48 h after the operation; measurements were thereafter assigned to three groups: severely elevated (ICP greater than 22 mmHg), mildly elevated (ICP = 14–22 mmHg), and normal (ICP ≤ 13 mmHg). Results: ONSD and Young's modulus for the ON and ONS of volunteers during VM were higher than those in the calm state (all P < 0.001). In contrast to ONSD, Young's modulus for ON and ONS did not correlate with age, body mass index, or sex. The best cutoff values of Young's modulus for ON for predicting elevated and severely elevated ICP were 16.67 kPa and 22.74 kPa, respectively. Accordingly, the sensitivity values were 96.7% and 88.9%, and the specificity values were 86.1% and 73.7%, which had the same diagnostic performance as ONSD. Conclusion: Young's modulus of the ON accurately reflects changes in ICP. It is not confounded by age, sex, or body mass index compared to ONSD.